2012
DOI: 10.1148/radiol.12112638
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Lobe Epilepsy: Quantitative MR Volumetry in Detection of Hippocampal Atrophy

Abstract: Purpose:To determine the ability of fully automated volumetric magnetic resonance (MR) imaging to depict hippocampal atrophy (HA) and to help correctly lateralize the seizure focus in patients with temporal lobe epilepsy (TLE). Materials and Methods:This study was conducted with institutional review board approval and in compliance with HIPAA regulations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
95
0
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(103 citation statements)
references
References 28 publications
5
95
0
3
Order By: Relevance
“…27 However, this has only been evaluated for the detection of hippocampal abnormalities on 1.5T scanners. 13 In 1.5T MRI, a good correlation of volume and signal abnormalities detected by quantification analysis and histopathology of HS has been demonstrated. 29 More recently, histologic studies have proposed that different patterns of neuronal loss in the hippocampus might be associated with different seizure outcome after surgical removal of the temporal lobe.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…27 However, this has only been evaluated for the detection of hippocampal abnormalities on 1.5T scanners. 13 In 1.5T MRI, a good correlation of volume and signal abnormalities detected by quantification analysis and histopathology of HS has been demonstrated. 29 More recently, histologic studies have proposed that different patterns of neuronal loss in the hippocampus might be associated with different seizure outcome after surgical removal of the temporal lobe.…”
Section: Discussionmentioning
confidence: 85%
“…Currently, most studies of hippocampal volumetry apply manual hippocampal delimitation, and whether manual 28 or automatic analysis has higher sensitivity and specificity is still debatable. 12,13 Despite this controversy, in the clinical context, the quantification of hippocampal abnormalities must be as fast and practical as possible. In this article, we used automated volumetry and a simple manual signal quantification in which it is necessary only to define a small region of interest in 3 sections of the T2 scan of each patient, without the need to define precisely the borders of the hippocampus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…24 Automated methods for the analysis of hippocampal volumetry have recently been published in clinical journals. 13,25 However, there have been few reports using an FDA-approved solution that could be practical in a busy clinical practice. Brewer et al 10 et al confirmed the existence of a natural asymmetry, with the right hippocampus found to be larger than the left hippocampus (4.00 versus 3.82 mL, 4.6% difference): The level of asymmetry they observed differed slightly from ours.…”
Section: Discussionmentioning
confidence: 99%
“…The steps involved include sequence-checking to ensure that appropriate high-resolution and contrast image parameters are performed, correction for field/gradient inhomogeneities, removal of the overlying calvaria, alignment to the probabilistic atlas of stereotypical anatomy, and segmented volumetry of predetermined anatomic areas derived from multiple subjects of multiple age groups (Brewer et al). [10][11][12][13] We sought to assess the value of NeuroQuant volumetry of the temporal lobe in patients with MTS with the added goal of trying to determine the difference in right and left hippocampal volumes that can be detected by experienced neuroradiologists in the clinical assessment of patients with temporal lobe epilepsy. We hypothesized that because radiologists assess the hippocampi for other imaging findings above and beyond volume loss alone, the neuroradiologist's determination of the correct side of the MTS would be more accurate than basic NeuroQuant volumetry.…”
mentioning
confidence: 99%